Quantum field theory of many-body systems : from the origin of sound to an origin of light and electrons - Wen, Xiao-Gang (Oxford graduate texts., 2004)
This is a pedagogical and systematic introduction to new concepts and quantum field theoretical methods in condensed matter physics which may have an impact on our understanding of the origin of light, electrons and other elementary particles in the universe. Emphasis is on clear physical principles.